Performance Test of Water Flow Control System and Nozzle Movement in Fountains Integrated with Automatic Plant Irrigation - Suhendra, Suhendra; Nopriandy, Feby; Fahrizal, Irma; Rianto, Ari (Universitas Muhammadiyah Metro, 2025)
The presence of fountains in public areas can create a comfortable atmosphere for everyone. Green spaces can provide ecological and aesthetic benefits, so fountains that combine ecological and aesthetic functions were essential. Based on this, research was conducted to test the performance of the water flow control system and nozzle movement control in a fountain integrated with automatic plant irrigation. Water flow testing was conducted by setting the dimmer at angles of 20°, 25°, 30°, 35°, 40°, 45°, 50°, 55°, 60°, and 65°. Nozzle movement testing was carried out by giving servo motor movement commands at angles of 50° – 130° and gradually adding an angle of 4° for each test. The data collected in the study were water flow and nozzle movement accuracy. Based on the test results, the minimum flow rate recorded was 0.141 l/s at an angle of 20°, the maximum flow rate reached 0.775 l/s at an angle of 65°, while the average flow rate from the tests was 0.490 l/s. The nozzle movement system showed an average accuracy of 98.84%, indicating that the system performs very well. The test results showed that the water discharge control and nozzle movement systems were able to produce controlled water jets, both in terms of flow rate and direction.